UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL DAUN SOYOGIK (Saurauia bracteosa DC) - Kadji, Miranty H; Runtuwene, Max R.J.; Citraningtyas, Gayatri (PHARMACON, 2013)
Soyogik (Saurauia bracteosa DC) is a plant in Actinidiaceae Families which isendemic in Indonesia, commonly found in Java and Bali. The aims of this research are toidentify the active compounds and determine the antioxidant activity of the leaf extractSoyogik. Soyogik leaves extracted by maceration and soxhlet using 70% ethanol as asolvent. The tests included quantitative test of antioxidant activity by DPPH method, andphytochemical test. The results show that maceration and soxhlet extract are containedphenolic compounds, steroids, flavonoids, and saponins. Both types of extract have powerfulantioxidant activity as showed on the IC50 values obtained. IC50 value of maceration andsoxhlet extract are 38,01 ppm and 28,18 ppm, respectively.Key word : phytochemical test, antioxidant, Saurauia bracteosa DC.